Work environment, reward and employee performance in banking sector: The mediating role of job satisfaction - Muhammad Asyraf, bestani (2023)
This study focuses on the effects of work environment and reward on employee’s performance in the banking sector in Penang. The research framework consists of employee performance as the dependent variable and two factors were examined as the independent variables namely, work environment and reward. In addition, job satisfaction is included as the mediator. A total of 300 questionnaires were distributed to the banks and only 280 were responded. Data collected were analysed by using Statistical Package for Social Sciences (SPSS) version 26. Statistical techniques such as regression analysis, correlation analysis, descriptive analysis and reliability analysis were used. The findings revealed that work environment, reward and job satisfaction were positively correlated to employee performance. Moreover, job satisfaction also mediates the relationship between work environment, reward and employee performance. Further, few implications and recommendations are suggested in this study.